DESIGNING E-CRM SYSTEM FOR BANKING INDUSTRY BASED ON WEB 2.0 TECHNOLOGY: A PROPOSAL - Hadjon, Ryan Peterzon; Wisnubhadra, Irya; Julianto, Eddy (Proceedings of KNASTIK, 2013)
Use of Customer Relationship Management (CRM) as a way to support marketing strategy is an important key to increase company’s profitability. Integration of classic CRM concepts and technology becomes new paradigm for success implementation of CRM. One way to accomplished this is by using web 2.0 technology. The innovation of web 2.0 which is based on user-oriented approach is a fit combination for CRM which is based on customer-oriented approach. This research was aimed to combine those two concepts for analyzing and designing an E-CRM system to help improved business marketing strategy in banking industry.